SMU’s School of Accountancy takes the lead in Asia to offer a suite of data analytics programmes to address industry needs - Singapore Management University (Institutional Knowledge at Singapore Management University, 2018)
The Singapore Management University’s (SMU) School of Accountancy (SoA) has announced a whole suite of data analytics programmes in order to address industry needs. These include a second major in Accounting Data and Analytics for undergraduates, the new Master of Science in Accounting (Data and Analytics), Graduate Certificate in Accounting Data & Analytics Programme and Certificate in Accounting Data & Analytics Programme.